Exploring women’s leadership communication styles and team effectiveness: A public university perspective - Latifah, Abdul Latif (2019)
Apparently, not much attention has been given to recording and critically assessing the leadership communication styles of these women, in Malaysia. Importantly, the pathways to leadership roles are seldom stated clearly. The research efforts focused specifically on three areas: (a) women leadership communication styles, (b) assumptions regarding women leadership traits, and (c) views on women leadership communication styles on team effectiveness. The qualitative research consisted of fieldwork involving in-depth interviews with ten informants, all occupying senior level positions in academics and non-academics categories within a university setting. All interviews were transcript and analyse using thematic analysis technique. Based on the analysis of data using NVivo, several of the identified themes emerged from the research indicated that women leaders in a university primarily incorporated leadership approaches that were in alignment with relational approaches to leadership; specifically, the informants tend to describe the tenets of transformational, transactional, democratic and autocratic communication leadership styles. The findings also indicated that the women leaders value the use of a distinctly people-centric, soft skill, masculine and feminine traits to their leadership towards team effectiveness; and were very comfortable in utilizing their gender differences in their roles. Majority of the informants stated that they were feeling themselves the most functional, whenever their women leaders are continuously showing support and relationship development in their leadership. Pertinent to theoretical implication generated from this study indicated that women leaders are highly effective when they use transformational and democratic leadership communication styles. While, the most dominant practical implication highlighted that women leaders’ constructive behavior can enhance their team member’s behaviors and attitude towards achieving team effectiveness. Finally, this research provides a platform and suggestions for future research in order to further investigate the effects of women leadership communication styles.